Association Between Left Ventricular Geometry and Renal Outcomes in Patients With Chronic Kidney Disease: Findings From Korean Cohort Study for Outcomes in Patients With Chronic Kidney Disease Study - Suh, Sang Heon; Oh, Tae Ryom; Choi, Hong Sang; Kim, Chang Seong; Bae, Eun Hui; Oh, Kook-Hwan; Lee, Joongyub; Jung, Ji Yong; Lee, Kyu-Beck; Ma, Seong Kwon; Kim, Soo Wan (Frontiers in Cardiovascular Medicine, 2022)
Background The impact of left ventricular (LV) geometry on the renal outcomes in patients with chronic kidney disease (CKD) has not been established yet. We aimed to investigate the association of LV geometry with renal outcomes and all-cause mortality in patients with pre-dialysis CKD. Methods A total of 2,144 subjects from the Korean Cohort Study for Outcome in Patients With Chronic Kidney Disease (KNOW-CKD) were categorized by LV geometry, which was defined by LV mass index and relative wall thickness [normal geometry, concentric remodeling, eccentric hypertrophy (eLVH), and concentric hypertrophy (cLVH)]. Study outcomes were composite renal events [decline of kidney function (the first occurrence of > 50% decline of eGFR or doubling of serum creatinine from the baseline) and onset of ESRD (initiation of dialysis or kidney transplantation) during follow-up periods)] and all-cause mortality. Results Cox regression analysis revealed that eLVH [adjusted hazard ratio (HR) 1.498, 95% confidence interval (CI) 1.197–1.873] and cLVH (adjusted HR 1.289, 95% CI 1.011–1.643) were associated with increased risk of composite renal events, whereas concentric remodeling (adjusted HR 1.881, 95% CI 1.135–3.118) and cLVH (adjusted HR 2.216, 95% CI 1.341–3.664) were associated with increased risk of all-cause mortality. Sensitivity analyses confirmed that concentric remodeling (adjusted HR 1.993, 95% CI 1.197–3.368) and eLVH (adjusted HR 1.588, 95% CI 1.261–2.001) are independently associated with all-cause mortality and composite renal events, respectively. Conclusion In conclusion, we report that LV geometry is significantly associated with adverse renal outcomes and all-cause mortality in patients with pre-dialysis CKD. Echocardiographic determination of LV geometry may help the early identification for the patients with high risk of CKD progression.